(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the socio-psychological characteristics of developing constructive thinking in students through group work in the technological education process. It is argued that group activity develops students’ abilities for analysis, idea exchange, and creative problem-solving by activating their cooperation, communication, and joint decision-making processes. The study highlights the psychological importance of social interaction, motivation, and teamwork skills in developing constructive thinking. The research employed a review of pedagogical and psychological literature, along with observations, interviews, and questionnaires. It was determined that group work, organized based on the practical, technology-oriented content of the curriculum, serves to develop students’ skills in understanding and analyzing problematic situations, developing effective solutions, and evaluating results. In particular, it was observed that during the group work on projects and problem-based tasks, students’ exchange of ideas, collaborative decision-making, and reflective activities were activated. The article also demonstrates that the positive psychological environment created during group work enhances students’ intrinsic motivation, increases their self-confidence, and fosters a positive attitude toward the learning process. The research findings confirm that the effective organization of group work in technology education is of great pedagogical importance, not only for students’ constructive thinking but also for their social activity, communication culture, and teamwork skills also have significant pedagogical importance for developing students’ social-psychological characteristics.